2021
DOI: 10.3390/molecules26216582
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizine/Indolizine-NSAID Hybrids: Design, Synthesis, Biological Evaluation, and Molecular Docking Studies

Abstract: In the current study, eight new hybrids of the NSAIDs, ibuprofen and ketoprofen with five pyrrolizine/indolizine derivatives were designed and synthesized. The chemical structures of these hybrids were confirmed by spectral and elemental analyses. The antiproliferative activities of these hybrids (5 μM) was investigated against MCF-7, A549, and HT-29 cancer cell lines using the cell viability assay, MTT assay. The results revealed 4–71% inhibition of the growth of the three cancer cell lines, where 8a,e,f were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Even though ibuprofen was not evaluated in this study, previous research has shown that it provides limited inhibitory effect against MCF-7 (Pedro-Hernández et al, 2017). Several amide derivatives of ibuprofen have shown enhanced antiproliferative effects when compared to the parent drug (Abourehab et al, 2021). This supports that dexibuprofen-amide derivatives are more effective in inhibiting MCF-7 than the parent drug, ibuprofen (He et al, 2021).…”
Section: Anticancer Activity Of Dexibuprofen-amide Derivativesmentioning
confidence: 54%
“…Even though ibuprofen was not evaluated in this study, previous research has shown that it provides limited inhibitory effect against MCF-7 (Pedro-Hernández et al, 2017). Several amide derivatives of ibuprofen have shown enhanced antiproliferative effects when compared to the parent drug (Abourehab et al, 2021). This supports that dexibuprofen-amide derivatives are more effective in inhibiting MCF-7 than the parent drug, ibuprofen (He et al, 2021).…”
Section: Anticancer Activity Of Dexibuprofen-amide Derivativesmentioning
confidence: 54%
“… 32 Encouraged by the above findings, Abourehab et al designed and synthesised a new series of hybrids by linking the pyrrolizine/indolizine derivatives with ibuprofen or ketoprofen NSAIDs. 33 These two scaffolds were selected based on their promising cytotoxic activity. The antiproliferative activities of these compounds/hybrids were investigated and showed 4–71% inhibition of the growth of three cancer cell lines, MCF-7, A549, and HT-29.…”
Section: Examples Of Hybrid Compoundsmentioning
confidence: 99%
“…7, the most active compounds, revealed IC 50 values of 7.6, 1.1, and 3.2 mM, respectively, against MCF-7 cells. 33 Non-viral gene therapy (NVGT)…”
Section: Anticancermentioning
confidence: 99%
“…In this work, the crystal structures of JAK kinases were visualized using the Discovery Studio Visualizer [ 47 ]. The crystals were prepared by removing water molecules following the previous reports [ 48 , 49 ]. Moreover, 2/3D binding modes of the JAK inhibitors into the co-crystallized kinases were visualized according to the previous report [ 50 ].…”
Section: Introductionmentioning
confidence: 99%